2020
DOI: 10.2151/jmsj.2020-070
|View full text |Cite
|
Sign up to set email alerts
|

Description and Attribution Analysis of the 2017 Spring Anomalous High Temperature Causing Floods in Kazakhstan

Abstract: This pre-publication manuscript may be downloaded, distributed and used under the provisions of the Creative Commons Attribution 4.0 International (CC BY 4.0) license. It may be cited using the DOI below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Several studies have explored the potential linkage between the precipitation extremes and the large-scale atmospheric circulation in CA, suggesting that the large-scale atmospheric circulation changes play a vital role in the changes of the precipitation amounts and extreme precipitation events 32,[42][43][44][45] . The large-scale atmospheric circulation is controlled by a series of large-scale climate indices, including the Atlantic Multidecadal Oscillation (AMO), North Atlantic Oscillation (NAO), Arctic Oscillation (AO), Pacific Decadal Oscillation (PDO) and El Nino-Southern Oscillation (ENSO).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the potential linkage between the precipitation extremes and the large-scale atmospheric circulation in CA, suggesting that the large-scale atmospheric circulation changes play a vital role in the changes of the precipitation amounts and extreme precipitation events 32,[42][43][44][45] . The large-scale atmospheric circulation is controlled by a series of large-scale climate indices, including the Atlantic Multidecadal Oscillation (AMO), North Atlantic Oscillation (NAO), Arctic Oscillation (AO), Pacific Decadal Oscillation (PDO) and El Nino-Southern Oscillation (ENSO).…”
Section: Discussionmentioning
confidence: 99%
“…Asia is also experiencing climate change due to global warming [4], and it has been predicted that precipitation patterns in China will include more frequent and severe precipitation patterns than those predicted in RCP8.5, a widely used climate change scenario model. Abnormal patterns have also been reported from Kazakhstan [5], where it was found that the increase in temperature due to global warming was a factor in the occurrence of flood damage. In addition, Weili et al (2015) [6] analyzed changes in precipitation in Japan, from 1901 to 2012, and found that precipitation has decreased considerably in recent decades, while Mohammad et al (2020) [7] reviewed annual climate change and evaluated associated trends in Iran from 1961 to 2010.…”
Section: Introductionmentioning
confidence: 68%
“…Flooding, among the most pervasive natural hazards, continues to pose substantial risks to human life and property worldwide (Rentschler et al 2022, Wang et al 2023. Although characterized by its archetypal arid nature, Central Asia, comprising Kazakhstan (KAZ), Kyrgyzstan (KGZ), Tajikistan (TJK), Turkmenistan (TKM), Uzbekistan (UZB) and China's Xinjiang (XJI), has been confronted with a recurring pattern of seasonal floods (Zou et al 2020, Wang et al 2022, resulting in substantial socioeconomic losses. Within the confines of TJK, the inundation incident of 1992 precipitated a lamentable toll of more than 1300 fatalities and inflicted economic damage amounting to nearly $500 million, which is approximately 23% of the country's gross domestic product (GDP) for the same year, as indicated by the World Bank Group (2016).…”
Section: Introductionmentioning
confidence: 99%